A population of CD4hiCD38hi T cells correlates with disease severity in patients with acute malaria - Apte, SH; Minigo, G; Groves, PL; Spargo, JC; Plebanski, M; Grigg, MJ; Kenangalem, E; Burel, JG; Loughland, JR; Flanagan, KL; Piera, KA; William, T; et al. (Wiley, 2020)
Objective: CD4+ T cells are critical mediators of immunity to Plasmodium spp. infection, but their characteristics during malarial episodes and immunopathology in naturally infected adults are poorly defined. Flow cytometric analysis of PBMCs from patients with either P. falciparum or P. knowlesi malaria revealed a pronounced population of CD4+ T cells co-expressing very high levels of CD4 and CD38 we have termed CD4hiCD38hi T cells. We set out to gain insight into the function of these novel cells. Methods: CD4+ T cells from 18 patients with P. falciparum or P. knowlesi malaria were assessed by flow cytometry and sorted into populations of CD4hiCD38hi or CD4norm T cells. Gene expression in the sorted populations was assessed by qPCR and NanoString. Results: CD4hiCD38hi T cells expressed high levels of CD4 mRNA and canonical type 1 regulatory T-cell (TR1) genes including IL10, IFNG, LAG3 and HAVCR2 (TIM3), and other genes with relevance to cell migration and immunomodulation. These cells increased in proportion to malaria disease severity and were absent after parasite clearance with antimalarials. Conclusion: In naturally infected adults with acute malaria, a prominent population of type 1 regulatory T cells arises that can be defined by high co-expression of CD4 and CD38 (CD4hiCD38hi) and that correlates with disease severity in patients with falciparum malaria. This study provides fundamental insights into T-cell biology, including the first evidence that CD4 expression is modulated at the mRNA level. These findings have important implications for understanding the balance between immunity and immunopathology during malaria.